MOTIVASI DAN PERILAKU PETANI DALAM PEMBUATAN GULA SEMUT DI KECAMATAN KOKAP KABUPATEN KULON PROGO - , HENI UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was done on Kokap Sub-district Kulon Progo Regency with the purpose to discover the motivation and behaviour of farmers in the âGula Semutâ production on Kokap, some factors that affect motivation in the âGula Semutâ production and to discover the effect of motivation to behaviour in the âGula Semutâ production. The method that was done in this research was analytical descriptive method. The location choice was done based on consideration that Hargotirtoâs Village, Hargorejoâs Village, Kalirejoâs Village, and Hargowilisâs Village are centers of industrial development âGula Semutâ. Each village was chosen 15 respondents by simple random sampling so that total sample as many as 60 respondents. The data was analyzed with proportion test, multiple linier regression, and simple linier regression. The result of this research showed that most farmers have a high motivation in the âGula Semutâ production. Most farmers have a good behaviour in the âGula Semutâ production for example producing organic âGula Semutâ without preservative. Experience, perception, and role of village officials positively affect motivation, the more experience of farmers gets motivation will be higher, the better perception of farmers gets motivation will be higher, and the stronger role of village officials gets motivation of farmers will be higher. Age, education, and market vallue do not affect motivation. Motivation positively affect farmers behaviour in the âGulaSemutâ production, the more motivation gets behaviour of farmers in the âGula Semutâ production will be better.